KNOWLEDGE AND PERCEPTION OF MONKEYPOX DISEASE IN YENAGOA, BAYELSA STATE (FUDMA JOURNAL OF SCIENCES, 2023)
Human monkey pox is an emerging viral zoonotic disease, which is caused by monkey pox virus. People living around the forested areas are more prone to the disease, possibly leading to sub-clinical infection. This study examined the level of awareness and perception of monkey pox disease in Yenagoa, Bayelsa State. Community awareness about monkey-pox varies from one region to another and also among cultures and this in turn affects the way people relate with victims of the disease. Primary and secondary data sources were used and data were analyzed using descriptive and inferential statistics (chi-square), and results were presented in frequency tables and percentages. The result of the findings revealed that 92% of the respondents representing the majority had some sort of information about monkey-pox, 55% of the 92 respondents that had information about the disease gave credit to radio/television as the major means of getting information. Health centers and family members also served as means of dispersing information about the disease, contributing about 30.8% and 8.3% respectively. Furthermore, the (chi-square) results with calculated value of 23.20 and tabulated value 7.18 indicated that the perception of respondents is dependent on their level of awareness and determines their reactions towards monkey pox disease. The study thus recommends adequate acquaintance of the public through sensitization, and seminar as key in creating awareness of the monkey-pox disease. The study concluded that government should provide sustainable monitoring team to keep check on the population and educate them on the importance of hygiene.
Keywords: Knowledge, Perception, Awareness, Monkey pox and Disease